Identification and Characterization of Non-aflatoxin Producing Aspergillus Species (Plant Bulletin, 2025)
Aflatoxins are secondary metabolites formed by Aspergillus species, mostly Aspergillus flavus and Aspergillus parasiticus. Among the mycotoxins that contaminate agricultural products, AFB1, AFB2, AFG1, AFG2, AFM1, and AFM2 are the most toxic and carcinogenic. Not all species of Aspergillus produce aflatoxins; some strains are non-toxin. It is estimated that about 1.6 billion dollars of the global food crops are thought to be mycotoxin contaminated. AFs contamination in maize grains is 10.0 µg/kg in central Punjab, Pakistan. It is a major global challenge to manage Aspergillus infection, biocontrol methods are most effective and innovative by applying non-aflatoxigenic spores onto the field prior to harvest. The study aimed to estimate the incidence of aflatoxin and to identify non-aflatoxin Aspergillus species in four Tehsils of Multan district. The survey in Multan district revealed varying incidence percentage across tehsils, the highest occurrence of A. flavus (26.21%) was recorded in Tehsil Multan while lowest (13.45%) incidence was found in Tehsil Multan Saddar. The use of CMA, AFPA and PDA media in this study enabled sufficient growth, sporulation and pigmentation, allowing for a thorough identification of aflatoxin and non-aflatoxin producing Aspergillus isolates. A. flavus and A. niger isolates on CMA media under UV light at 365 nm were screened, 19 out of 20 isolates showed blue fluorescence while non-aflatoxigenic A. niger showed none. On AFPA media, A. flavus isolates indicated orange coloration underside their colonies which were aflatoxin producing and A. niger isolate did not show any coloration and considered as non-aflatoxin Aspergillus isolate. While on PDA media, the 7 days old isolates of A. flavus were detected through Ammonia Vapor Test (AVT) with a drop of concentrated ammonia hydroxide turned plum red indicating aflatoxin and A. niger showed no color change and confirmed as non-aflatoxin producing Aspergillus isolate. The use of selective media like CMA and AFPA were effective for morphological identification by distinguishing between aflatoxigenic and non-aflatoxigenic isolates when advance tools were accessible. Incorporating non-aflatoxin producing A. niger strain into crop management can reduce the risk of aflatoxin contamination, improving food safety and economic stability.
Keywords: Aspergillus flavus; Aspergillus niger; Disease incidenc; UV light screening; AFPA media; Ammonia vapor test